Tri(1-adamantyl)phosphine: Exceptional Catalytic Effects Enabled by the Synergy of Chemical Stability, Donicity, and Polarizability - Carrow, Brad P.; Chen, Liye (Synlett, 2017)
Tri(1-adamantyl)phosphine, a simple yet long-absent homoleptic phosphine, has finally been prepared. The simplicity of this compound beguiles its exceptional properties. The electron-releasing character eclipses all other alkylphosphines. The phosphine geometry and overall size are also more compact than anticipated, which may occur as a result of dispersion forces. We believe the donicity, marked resistance towards cyclometallation or P−C bond scission, and also substantial polarizability engendered by the three diamondoid fragments together account for the phenomenal performance of Pd-PAd3 catalysts during Suzuki–Miyaura coupling reactions. A correlation analysis is also described that provides support for polarizability as a potentially general influence on the properties of tertiary phosphines.1 Introduction2 Synthesis of Tri(1-adamantyl)phosphine3 Reactions of Tri(1-adamantyl)phosphine Palladium Complexes4 Electronic and Steric Properties of Tri(1-adamantyl)phosphine5 Conclusion
Keywords: phosphine; ligand; catalysis; cross-coupling; palladium; diamondoid